Development of Intercultural-Based Speaking Materials for 7th-Grade Junior High School Students in the Merdeka Curriculum - Ni Kadek Karunia Putri Permatasari; Luh GD Rahayu Budiarta, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2025)
This study aims to develop intercultural-based speaking materials for 7th-grade junior high school students within the framework of Indonesia’s Merdeka Curriculum. The materials are designed to enhance students’ speaking abilities while integrating intercultural competence and peace education. Utilizing the Successive Approximation Model (SAM), the study employs a mixed-method approach, including surveys, document analysis, and expert evaluations. Findings reveal a strong student preference for engaging, interactive, and culturally relevant speaking activities. The materials underwent multiple revisions based on expert feedback to ensure alignment with the Merdeka Curriculum’s emphasis on inclusivity, critical thinking, and communication skills. The final version of the materials includes activities that not only improve linguistic competence but also foster cultural awareness and peacebuilding among students. This research highlights the significance of integrating intercultural elements into language education, particularly in diverse and conflict-prone regions. The results suggest that such materials can significantly contribute to creating a more inclusive and empathetic learning environment that prepares students to engage effectively in a multicultural society. Further studies should explore the long-term impact of these materials on students’ intercultural competence and peace education